FROM INSTRUCTION TO INSPIRATION: THE ROLE OF TEACHERS IN FOSTERING A GROWTH MINDSET IN HIGH SCHOOL STUDENTS - Rensi Bulung; Dameria Sinaga (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Education must extend beyond academic achievement to foster character, critical thinking, and resilience in facing challenges. This study examines the role of teachers in promoting a growth mindset—the belief that abilities can be developed through effort and learning—and explores student responses to such approaches. Conducted at SMA Negeri 3 Tana Toraja, South Sulawesi, this qualitative research used semi-structured interviews, participatory observation, and documentation to gather data from teachers and students between March and June 2025. Findings reveal that teachers effectively nurture a growth mindset by implementing strategies such as open-ended and reflective questioning, differentiated instruction, sharing inspirational stories, and cultivating supportive peer interactions. These approaches encourage students to value the learning process, embrace challenges, and perceive failures as opportunities for growth. In response, students demonstrated increased confidence, greater classroom participation, and enhanced motivation toward learning. The study concludes that teachers play a dual role as both instructors and inspirers, shaping students' mindsets and fostering environments where resilience and potential can flourish. Recommendations include the consistent integration of growth mindset strategies into teaching practices to support holistic student development. This research highlights the importance of teacher-driven initiatives in creating learning experiences that prioritize psychological and academic growth.